Assessing the chelating ability of Aerva lanata: adsorption of chromium from tannery effluent and its toxicity measurement - Poonkuzhali, K.; Manivannan, M.; Palvannan, T. (Химия и технология воды, 2013)
The chelating ability of aqueous leaf extract of Aerva lanata was assessed in vitro. The aqueous leaf extract showed a dose dependent decrease in chelating ability using FeCl₂. The highest chelating ability of aqueous leaf extract was observed at 2•10⁻⁵ g/mL (100 ± 0.00). The antioxidant activity of the aqueous leaf extract ranged from 42.13% to 88.66%. At 2•10⁻⁵ g/mL concentration, a strong positive significant correlation was observed between chelating ability and total phenolics concentration (R = 0.94; P = 0.001). The chelating ability of aqueous leaf extract (2•10⁻⁵ g/mL) showed a high positive significant correlation with antioxidant activity (R = 0.78; P = 0.001). Aqueous leaf extract removed the chromium from tannery effluent by 43 mg/g. Allium cepa toxicity test was performed on tannery effluent treated with aqueous leaf extract that increased the root length of onion.